Ancient Greek housing - Nevett, Lisa C. (Cambridge ; New York, NY)
xix, 329 sayfa
Keywords: “Provides students of Classics, ancient history and archaeology with an accessible introduction to the archaeological evidence for housing and domestic life in the ancient Greek world. Numerous illustrations (line drawings and photographs), along with texts in translation, enable readers to engage closely with the topic“ --